Upin and Ipin's Film Homely Life Education Al-Qur'an Perspective - Siti Lailiyah; Robingun Suyud El Syam (Reflection : Islamic Education Journal, 2025)
The film Upin and Ipin contains many good lessons to study, but no one has studied the characteristics of a simple life that characterizes the film. This article aims to reveal education about the simple life of the film Upin and Ipin from the perspective of the Qur'an. The author uses qualitative methods with descriptive analysis, with the main data source being the animated film Upin and Ipin, and supported by secondary sources in the form of journal articles, books, interpretations of the Al-Qur'an and web sources, which support the data to strengthen the arguments in the analysis. The animated film Upin and Ipin is an education on simple living that is in line with the conception of the Qur’an. For the Qur'an, the birth of humans, society, culture, civilization, language, race, tribe and clan as well as the fall of nations are signs that humans must ponder and learn from, so that the Qur'an. A modest life as referred to in the Qur'an includes not being excessive and not being too stingy, therefore, people who distribute their wealth to people in need are good people. Allah SWT through the Qur'an has ordered His servants to live modestly. This is because by living simply, humans can control their lives and not fall into hedonistic lifestyles that tend to lead humans into traps. In this way, the education of modest living contained in the film Upin and Ipin is in line with the conception of the Qur'an. The research implications of the importance of moderation in life create a stable and flexible life.